2017
DOI: 10.1021/acsami.7b01209
|View full text |Cite
|
Sign up to set email alerts
|

Chained Iron Microparticles for Directionally Controlled Actuation of Soft Robots

Abstract: Magnetic field-directed self-assembly of magnetic particles in chains is useful for developing directionally responsive materials for applications in soft robotics. Using materials with greater complexity allows advanced functions, while still using simple device architectures. Elastomer films containing chained magnetic microparticles were prepared through solvent casting and formed into magnetically actuated lifters, accordions, valves, and pumps. Chaining both enhances actuation and imparts a directional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 40 publications
0
104
0
Order By: Relevance
“…d) Optical images of magnetic elastomer films employed in accordions, lifters, and peristaltic pumps. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Materials Derived From Ferrofluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…d) Optical images of magnetic elastomer films employed in accordions, lifters, and peristaltic pumps. Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Materials Derived From Ferrofluidsmentioning
confidence: 99%
“…It was found that these helical micromotors could display rotation and corkscrew motion responding to a clockwise and 3D rotary magnetic field, respectively. Besides, Schmauch et al embedded chained ferromagnetic nanoparticles into thin elastomer films via solvent casting . The resultant films were then formed into accordions, lifters, and peristaltic pumps and showed excellent magnetic response (Figure d).…”
Section: Materials Derived From Ferrofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…To introduce additional functionalities, magnetic‐responsive IONPs are combined to the optically responsive G@UCNPs hydrogel to produce a multifunctional hydrogel, using the magnetic self‐assembly of IONPs in hydrogel to introduce anisotropy at the meso‐ and nanoscale . The G@UCNPs were printed with an empty inner portion, which acts as assembly chamber for the magnetic nanoparticles (Figure ).…”
mentioning
confidence: 99%
“…To introduce additional functionalities, magnetic-responsive IONPs are combined to the optically responsive G@UCNPs www.advancedsciencenews.com www.advintellsyst.com hydrogel to produce a multifunctional hydrogel, using the magnetic self-assembly of IONPs in hydrogel to introduce anisotropy at the meso-and nanoscale. [4,30,41] The G@UCNPs were printed with an empty inner portion, which acts as assembly chamber for the magnetic nanoparticles (Figure 1). The outer cases composed of G@UCNPs, which is solid at T < 37 C, was filled up with a solution of PEGDA monomer (liquid), the photoinitiator Irgacure 2959 (3 mg mL À1 ), and IONPs (%2.5 mg mL À1 ).…”
mentioning
confidence: 99%